A clinical experience of 'STAMP' plate-guided Bonebridge implantation. (October 2014) - Takumi, Yutaka; Matsumoto, Nozomu; Cho, Byunghyun; Ono, Hidenori; Mori, Kentaro; Tsukada, Keita; Ichinose, Aya; Yoshimura, Hidekane; Iwasaki, Satoshi; Komune, Shizuo; Usami, Shin-ichi
Abstract Conclusion: The surface template-assisted marker positioning (STAMP) method is useful for successful Bonebridge™ (BB) implantation on a planned site while avoiding dangerous positions. Objectives: To confirm the usefulness of the STAMP method for the safe operation of BB. Methods: From a patient's temporal bone CT data, a guide plate and confirmation plate were generated by the STAMP method. The guide plate is used to mark the correct place for implantation, while the confirmation plate lets us know the correct angle and depth of the hole. Results: With the guide plate, the correct place for BB implantation was easily found. The hole was made to be an appropriate size with the confirmation plate while exposing only a small part of sigmoid sinus as simulated. Finally, the BB implant was successfully placed exactly at the planned site.